Espiritualidade e estilo de vida: contribuições éticas, econômicas e sociais a partir do evangelho de Lucas - Barbosa, João Cândido (2017)
This thesis aims to investigate, from the Luke's Gospel, the political and socioeconomic situation of the people during the first century. It deals with situations that affected the lives of impoverished, marginalized and despised people in the context of a society under the power of the Roman Empire, which ditacted the economic rules at that time. It is understood that the Luke's Gospel tells the history lived by the original christian communities with their ethical and spiritual values regarding God's Kingdom and the lifestyle by them adopted, against the patriarchal system imposed due to the Roman domination. The work highlights the conflicts that existed in the time of Jesus and the writing of the Luke's Gospel. In this scenario, dominated by the wishes of the powerful ones to the detriment of the weak and impoverished, the path chosen by Jesus was to stay at the side of weak, despicable and despised ones, and all who sought to change their lives. Jesus' liberating praxis confronted the Jewish elite and the Roman Empire, proposing the ideological liberation from the oppressive imposition that subjugated and enslaved people through exorbitant tax levels and the force of the Roman army, which destroyed countless lives with refined cruelty. It analyzes the pericopes that tell the story of the widow of Naim (7,11-17), the parable of the good samaritan (10,25-37) and the Zacchaeus narrative (19,1-10), analyzed under its ethical and socioeconomic elements. In this context, it is perceived that the Jesus spirituality and ethics are based in the concept of God as a Father, invoked by prayer, from which compassion and mercy are originated, and that are extended to the needy people. Therefore, it is argued that Jesus' actions are capable of reversing death processes in life processes and can contribute to a living in society with more dignity and social justice, also in nowadays.